Developing the enterprise architecture for the Namibian government. Issue 3 (19th April 2018) - Shaanika, Irja; Iyamu, Tiko
Abstract: The Namibian government strive to use the enterprise architecture (EA), to address the incidents of disparities, such as obsolesce, incompatibility, duplications, lack of uniformity, and integration challenges that hampers processes and activities in providing socioeconomic services to the communities of the country. Through its domains, the aim of the EA is to facilitate services towards transformation, development, and growth of socioeconomic activities in the country. However, the deployment of the EA is a challenge because there are implications of practice, which are constraints to the aim of the concept. The objective of this study was therefore to develop a framework, which can be used to guide the deployment of the EA. Based on the framework, we examine the implications of practice, which is intended to improve service delivery through the deployment of the EA. The qualitative methods were used in the study. The semi‐structure technique was applied to collect qualitative data. Based on the findings from the data analysis, a framework was developed, which depicts how the EA is influenced by interactions and relationships that happens between the involved actors, and draws on the implications for services delivery. This study is important to both academic and government, as it reveals on how certain factors manifests themselves, to enable, and at the same time, constrain processes and activities of information systems and technologies.